Mapping evapotranspiration trends using MODIS and SEBAL model in a data scarce and heterogeneous landscape in eastern Africa - Kiptala, J.K.; Mohamed, Y.; Mul, Marloes L.; Zaag, P. van der (Wiley, 2013)
[1] Evapotranspiration (ET) accounts for a substantial amount of the water use in river basins particular in the tropics and arid regions. However, accurate estimation still remains a challenge especially in large spatially heterogeneous and data scarce areas including the Upper Pangani River Basin in Eastern Africa. Using multitemporal Moderate-resolution Imaging Spectroradiometer (MODIS) and Surface Energy Balance Algorithm of Land (SEBAL) model, 138 images were analyzed at 250 m, 8 day scales to estimate actual ET for 16 land use types for the period 2008–2010. A good agreement was attained for the SEBAL results from various validations. For open water evaporation, the estimated ET for Nyumba ya Mungu (NyM) reservoir showed a good correlations (R = 0.95; R2 = 0.91; Mean Absolute Error (MAE) and Root Means Square Error (RMSE) of less than 5%) to pan evaporation using an optimized pan coefficient of 0.81. An absolute relative error of 2% was also achieved from the mean annual water balance estimates of the reservoir. The estimated ET for various agricultural land uses indicated a consistent pattern with the seasonal variability of the crop coefficient (Kc) based on Penman-Monteith equation. In addition, ET estimates for the mountainous areas has been significantly suppressed at the higher elevations (above 2300 m a.s.l.), which is consistent with the decrease in potential evaporation. The calculated surface outflow (Qs) through a water balance analysis resulted in a bias of 12% to the observed discharge at the outlet of the river basin. The bias was within 13% uncertainty range at 95% confidence interval for Qs. SEBAL ET estimates were also compared with global ET from MODIS 16 algorithm (R = 0.74; R2 = 0.32; RMSE of 34% and MAE of 28%) and comparatively significant in variance at 95% confidence level. The interseasonal and intraseasonal ET fluxes derived have shown the level of water use for various land use types under different climate conditions. The evaporative water use in the river basin accounted for 94% to the annual precipitation for the period of study. The results have a potential for use in hydrological analysis and water accounting.